PENGARUH HUMAN RELATIONS TERHADAP KINERJA PEGAWAI DI DINAS PENDIDIKAN KOTA GUNUNGSITOLI - Zebua, Kristiawan; Fatolosahulu (Jurnal Tunas Pendidikan, 2024)
At the Gunungsitoli City Education Office, researchers found that interpersonal harmony (human realtions) among employees, especially in the context of public services, is still inadequate. Although the services are directly related to the community, employees tend to carry out their duties individually rather than as a team. The imbalance of communication among employees hinders the effectiveness of services, so the concept of human relations is not optimally applied. it is important for leaders to integrate the principles of human relations into the work system. This aims to create an attitude of humanism among employees, unify employee perceptions and ensure that work is done collaboratively, not just as individuals. This approach is necessary to achieve satisfactory work results. The purpose of this study was to determine the effect of human relations on improving employee performance at the Gunungsitoli City Education Office, data collection techniques by means of observation, and distributing questionnaires to 48 respondents of Gunungsitoli City Education Office employees. While testing data analysis using validity test, reliability test, correlation coefficient analysis, coefficient of determination, and hypothesis testing. In this study using quantitative research with data calculations using SPSS to obtain accurate values. The results of this study, the t test of variable X human relations is 5.561 with a significance level of 5% in the t table of 1.677. It is known that the Sig value = 0.000 <0.05. Then according to the interpretation: If the Sig value <0.05 or t count> t table then there is an influence between variable X on variable Y, otherwise, if the Sig value> 0.05 or t count < t table then there is no influence between variable X on variable Y. So it can be concluded that the influence of Human Relations is positive and significant on performance. In the results of the calculation of the coefficient of determination (R-Square) of human relations on performance, it can be concluded that the amount of influence of human relations on performance is 38.1. For 61.9% influenced by other factors not discussed in this study.